Interaction of Media and Politics in the Baltic States - fakultetas, Komunikacijos (Žurnalistikos tyrimai, 2015)
Vilnius University, Faculty of Communication (Saulėtekio 9), 7-8 May 2015 The international scientific conference “Interaction of Media and Politics in the Baltic States”, held on May 7–8, 2015 at Vilnius University’s Faculty of Communication, focused on the interplay between media policy, information warfare, propaganda, political communication, and journalism in the Baltic region. Scholars from Lithuania, Latvia, Estonia, Finland, Poland, Sweden, and the UK discussed issues such as the creation of public service media, media self-regulation, the role of negativity and popularity in political discourse, professional journalism training, and Russia’s information strategy targeting the Baltic States. The conference emphasized the geopolitical role of media in shaping democratic resilience.